Towards Migration-Responsive Local Government: Profiling, Perceived Program Needs and Driving Forces - Rabino, Evelyn; Montalbo, Meynardo (JPAIR Multidisciplinary Research, 2019)
The phenomenon of ethnic migration has been part of human history and vital to the development of cultures and civilizations. Using mixed-method inquiry, the research studied the Local Government’s responsiveness to the Muslim migrants’ need for programs relative to education, livelihood, health, and sanitation, housing, socio-civic, and cultural aspects, including investigation of the driving forces of the 155 migrants selected using purposive sampling. Quantitative and qualitative data were analyzed, and in addition, a subset of the participants, which included government personnel and leaders of the Muslims, were interviewed. The use of documentary analysis and observation of Muslim activities were also vital sources of data. Results showed that older migrant females have migrated for a relatively long time who have been engaged in business and trading operations, considered limited opportunities and personal reasons as driving forces of their migration; the local government’s support for the educational needs of the Muslims through Madrassah School supervised by the Department of Education, support for livelihood program, and promoting harmonious relationships between Muslims and non-Muslims through sociocultural and other programs. Results would lead to the creation of academe government linkage for a sustainable development program for Muslim migrants.